2007
DOI: 10.1016/j.ijsolstr.2007.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of buckling characteristics of carbon nanotubes

Abstract: In this paper, to investigate the buckling characteristics of carbon nanotubes, an equivalent beam model is first constructed. The molecular mechanics potentials in a C-C covalent bond are transformed into the form of equivalent strain energy stored in a three dimensional (3D) virtual beam element connecting two carbon atoms. Then, the equivalent stiffness parameters of the beam element can be estimated from the force field constants of the molecular mechanics theory. To evaluate the buckling loads of multi-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Type I continuum shell model requires parameters such as Young's modulus E, Poisson's ratio m, and shell thickness h; which are usually calibrated from MD simulation results. In Type II shell model, the equilibrium equations are derived by minimizing the total potential energy of the CNT (Ansari and Rouhi 2010;Belytschko et al 2002;Cheng et al 2009;Hu et al 2007;Li and Chou 2003;Lu et al 2010).…”
Section: Continuum Shell Modelsmentioning
confidence: 99%
“…Type I continuum shell model requires parameters such as Young's modulus E, Poisson's ratio m, and shell thickness h; which are usually calibrated from MD simulation results. In Type II shell model, the equilibrium equations are derived by minimizing the total potential energy of the CNT (Ansari and Rouhi 2010;Belytschko et al 2002;Cheng et al 2009;Hu et al 2007;Li and Chou 2003;Lu et al 2010).…”
Section: Continuum Shell Modelsmentioning
confidence: 99%
“…Their results are in good agreement with the results of MD computations. Hu et al [16] used the molecular structural mechanics approach, which uses the 3D beam elements for modeling of interatomic bonds of C-C and rod elements for modeling of van der Waals forces. They concluded that their model is adequate for prediction of the buckling load of single-and multi-walled CNTs with long length.…”
Section: Introductionmentioning
confidence: 99%
“…Yakobson et al [13] simulated the compression of an SWCNT through MD and predicted the Young's modulus of SWCNTs about 5.5 TPa with the effective wall thickness of 0.066 nm. Hu et al [14] proposed an improved molecular structural mechanics method for the buckling analysis of carbon nanotubes, based on Li and Chou's model [9] and Tersoff-Brenner potential [12]. Yao and Han [15] studied the thermal effect on axially compressed buckling of a MWCNT, using continuum mechanics.…”
Section: Introductionmentioning
confidence: 99%